Anomaly Pasar Pada Bursa Efek Indonesia (Jurnal Tepak Manajemen Bisnis, 2015)
Abstract. This paper primarily aims to investigate the seasonality of weekly and monthly stock returnsin an emerging stock market of Indonesia. Evidence on return seasonality and January effect wouldhave important implications for investment strategies to gain abnormal returns and it would invalidatethe paradigm of the efficient markets hypothesis. For the period 2010 -2014, daily returns on theIndonesia Stock Exchange (IDX) are employed. Untuk mengetahui ada tidaknya anomali montly effectdi BEJ. analysis using two statistical analysis, test analysis of two average difference using independentsample t test and simple linear regression analysis.we found no evidence of Weekly and monthly seasonality as well as January effect in the IDX returns.These results indicate that investors cannot take any advantage of information about the month of theyear when investing in the ASE to gain abnormal returns. On other words, these new findings indicatethat investors in the IDX should not consider the seasonal effects when constructing their portfolio.Key Word: Indonesia stock exchange, Anomaly, Monthly Effect